PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN PMRI PENGUKURAN, LUAS, DAN VOLUME DI SEKOLAH DASAR - Umi Nur Kholifah; Lola Indra Mukti; Helis Ira Setiawati; Eka Zuliana (Jurnal Karya Pendidikan Matematika, 2024)
This research aims to test the learning design that has been designed by developing and improving things that still hinder the learning process of measurement, area and volume material in class IV students at SDN Purworejo 01. The method used in this research uses design research which was carried out in Class IV students at SDN Purworejo with a total of 11 students consisting of 3 female students and 8 male students. The data collection technique in this research is observation which consists of observations for one-on-one and small group trials, documentation and field notes, as additional data, namely interviews. The results of this research show 3 out of 11 students still cannot understand the material regarding measurements, area and volume and only 8 students can understand this material.